2014
DOI: 10.1002/ejlt.201300462
|View full text |Cite
|
Sign up to set email alerts
|

Ovary and egg fatty acid composition of greater amberjack broodstock (Seriola dumerili) fed different dietary fatty acids profiles

Abstract: The aim of this study was to assess the effect of an experimental diet (ED), with high levels of 18:1 n-9 and low eicosapentaenoic to arachidonic acid ratio (EPA/AA), on the fatty acid (FA) profile of ovary and eggs of Seriola dumerili broodstock, in contrast to a non-specific commercial diet (nsCD), taking wild fish lipid composition as a positive reference. Two groups of Seriola broodstock born in captivity were fed with either the ED or the nsCD during two consecutive spawning seasons (21 months). After 7 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 50 publications
(72 reference statements)
4
22
0
Order By: Relevance
“…The dietary deficiency of ARA and DHA also decreased tissue ARA/EPA and DHA/EPA physiological balances. Similar results related to dietary fatty acid inputs have been reported in several tissues of captive and wild white seabream ( Diplodus sargus ), black seabream ( Spondyliosoma cantharus ), yellowtail ( Seriola lalandi ) and females of greater amberjack at spawning [31, 32, 113115]. Studies by Asturiano et al [36] showed that male European sea bass Dicentrarchus labrax fed commercial diets enriched in highly unsaturated fatty acids (HUFA) such as DHA and EPA, exhibited more successful reproductive performance in terms of duration of spermiation, total milt production, milt spermatozoa density, and fertilization than fish fed with a non-enriched diet.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…The dietary deficiency of ARA and DHA also decreased tissue ARA/EPA and DHA/EPA physiological balances. Similar results related to dietary fatty acid inputs have been reported in several tissues of captive and wild white seabream ( Diplodus sargus ), black seabream ( Spondyliosoma cantharus ), yellowtail ( Seriola lalandi ) and females of greater amberjack at spawning [31, 32, 113115]. Studies by Asturiano et al [36] showed that male European sea bass Dicentrarchus labrax fed commercial diets enriched in highly unsaturated fatty acids (HUFA) such as DHA and EPA, exhibited more successful reproductive performance in terms of duration of spermiation, total milt production, milt spermatozoa density, and fertilization than fish fed with a non-enriched diet.…”
Section: Discussionsupporting
confidence: 77%
“…Other phospholipids, including PC, contain high levels of DHA, which is the most relevant essential fatty acid in egg quality [107]. The importance of PC, PE and n-3 HUFA, as well as of DHA/EPA/ARA ratios on gonad development and egg quality has been highlighted by many authors [31, 32, 3335, 121124]. In fact, two thirds of the lipid fraction in vitellogenin is made of PC [107] that is also the main phospholipid in mature ovaries and fertilised eggs [125].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, females at prespawning stage presented higher lipid content in all sampled tissues, with a marked increase in dorsal muscle. Dorsal muscle lipid content was higher in our samples (24.04%) when compared to the results found in the muscle of S. fasciata at the same maturation stage (Nogueira et al, 2016) and of S. dumerilli (Haouas, Zayene, Guerbej, Hammami, & Achour, 2010;Rodríguez-Barreto et al, 2012), but similar to those found by Rodríguez-Barreto et al (2014) in indoor cultivated S. dumerilli. Such differences highlight the need of knowing fish nutritional value, especially when fish are not easy to distinguish, as is the case between Almaco jack adults and greater amberjack juveniles.…”
Section: Total Lipidsupporting
confidence: 79%